Cryo‐EM structures of pentameric autoinducer‐2 exporter from Escherichia coli reveal its transport mechanism. (14th June 2022) - Khera, Radhika; Mehdipour, Ahmad R; Bolla, Jani R; Kahnt, Joerg; Welsch, Sonja; Ermler, Ulrich; Muenke, Cornelia; Robinson, Carol V; Hummer, Gerhard; Xie, Hao; Michel, Hartmut
Abstract: Bacteria utilize small extracellular molecules to communicate in order to collectively coordinate their behaviors in response to the population density. Autoinducer‐2 (AI‐2), a universal molecule for both intra‐ and inter‐species communication, is involved in the regulation of biofilm formation, virulence, motility, chemotaxis, and antibiotic resistance. While many studies have been devoted to understanding the biosynthesis and sensing of AI‐2, very little information is available on its export. The protein TqsA from Escherichia coli, which belongs to the AI‐2 exporter superfamily, has been shown to export AI‐2. Here, we report the cryogenic electron microscopic structures of two AI‐2 exporters (TqsA and YdiK) from E. coli at 3.35 Å and 2.80 Å resolutions, respectively. Our structures suggest that the AI‐2 exporter exists as a homo‐pentameric complex. In silico molecular docking and native mass spectrometry experiments were employed to demonstrate the interaction between AI‐2 and TqsA, and the results highlight the functional importance of two helical hairpins in substrate binding. We propose that each monomer works as an independent functional unit utilizing an elevator‐type transport mechanism. Synopsis: Bacteria communicate by releasing chemicals known as autoinducers; these autoinducers can modify colony behavior. This article describes the structure of two autoinducer‐2 (AI‐2) exporters from E. coli, proposing a mechanism for their activity. Cryo‐EM reveals the AI‐2 exporters TqsA and YdiK form pentameric protein complexes. Two helix–turn–helix motifs mediate substrate binding suggesting an elevator‐like transport mechanism. A similar mechanism to glutamate transporters is proposed in which each protomer works independently. Abstract : Cryo‐EM structures of two autoinducer‐2 exporters give important insights into how bacteria communicate with each other.